2016
DOI: 10.1118/1.4940790
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculated correction factors for the PTW microDiamond detector in the Gamma Knife‐Model C

Abstract: Similar to what has been found in the Gamma Knife Perfexion, the PTW microDiamond over-responds in the smallest 4 mm field. The over-response can be corrected via the Alfonso formalism using the correction factors determined in this work. Using the MC calculated correction factors, the PTW microDiamond detector is an effective dosimeter in all available helmet sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…The PTW 60019 microDiamond detector has been extensively studied for small field dosimetry. [24][25][26][27][28]37,38 For the 4 mm diameter cone used in this study, the ROF calculated using the zero area extrapolation technique was in good agreement to the ROF measured with the microDiamond detector. As such, we believe this agreement shows the suitability of using a zero area technique for these smaller fields in film dosimetry.…”
Section: Scan Resolutionsupporting
confidence: 69%
See 1 more Smart Citation
“…The PTW 60019 microDiamond detector has been extensively studied for small field dosimetry. [24][25][26][27][28]37,38 For the 4 mm diameter cone used in this study, the ROF calculated using the zero area extrapolation technique was in good agreement to the ROF measured with the microDiamond detector. As such, we believe this agreement shows the suitability of using a zero area technique for these smaller fields in film dosimetry.…”
Section: Scan Resolutionsupporting
confidence: 69%
“…A best fit extrapolation technique was applied to the results to determine the zero area output factor utilizing a second order polynomial or linear function based on cone size and data requirements. Relative output factor measurements determined with a PTW 60019 microDiamond detector [24][25][26][27][28] (PTW, PTW-Freiburg, Germany) have also been included for comparison with the extrapolated Gafchromic EBT3 results. These measurements were made under the same geometrical conditions as the measurements for the Gafchromic EBT3 film.…”
Section: A Film Dosimetry Techniquementioning
confidence: 99%
“…The results of one study investigating RapidArc (arc modulated delivery, Varian Medical Systems) for SRS indicated that for a 0.4 cm 3 target, their measured dose was 20% higher than the treatment planning system (TPS)-planned dose even when using a 1.25-mm dose calculation grid. 78 For PFX, 42,43,[79][80][81][82][83][84] CK with cone inserts, 56,[85][86][87][88][89][90][91][92][93][94] or linac with cone inserts, small-field dosimetry is also challenging; however, the discrete nature of the fixed collimator sizes in such dedicated systems minimizes the risk of user-dependent beam modeling error and focuses more user attention to verifying a finite set of dosimetric properties rather than modeling them. The clinical relevance of over-or underdosing in the context of multiple metastases SRS is unknown, as there are limited outcome data available; however, a factor when considering systems may be how susceptible a given system is to dosimetric error.…”
Section: Multiple (>4) Metastasesmentioning
confidence: 99%
“…If the machine is incapable of producing such a field, a machine-specific reference (MSR) field is used instead, taken to be the largest available field (e.g., 60 mm diameter circular field for CyberKnife). This formalism has been applied extensively for 55 individual field configurations, with several authors having calculated k f clin ,fmsr Q clin ,Qmsr correction factors in small individual fields (Cranmer-Sargison et al 2012, Ralston et al 2012, Scott et al 2012, Czarnecki & Zink 2013, Bassinet et al 2013, Azangwe et al 2014, Benmakhlouf et al 2014, Francescon, Beddar, Satariano & Das 2014, Francescon, Kilby & Satariano 2014, Moignier et al 2014, Barrett & Knill 2016.…”
Section: Introductionmentioning
confidence: 99%